Diagramas de estructura en el análisis de varianza (2007)
ABSTRACT: Diagrams of structure were defined by Taylor Jr and Milton for standard experimental balanced designs. The method requires recognizing the characteristics of the set of factors used in the interaction or nested. The expected main square, the F Ratio and the estimated variance components can be driven by using diagrams of structure symbols. Diagram of structure facilitates understanding the design of experimental classification and hypotheses associated with the above mentioned model, it is a visual representation that allows understanding the relationship or existing interactions between the factors selected by the researcher.